Perceived Ethical Value of Brand and Online Customers’ Shopping Experience: The Moderating Role Of Employee Resilience and The Mediating Role Of Brand Relationship Quality in Iraq Smartphone Users - Saif Ali Jasim (Indonesian Journal Publisher, 2025)
The current study explores customer relationships among Iraq Smartphone Users by measuring the level of relationship between perceived ethical value of the brand and Online Customers’ Shopping Experience and the quality of their relationship with it, in addition to studying the moderating effect of Employee Resilience. Data was collected from (453) Iraq Smartphone Users, and to address the study's problem, the descriptive analytical method was adopted. A questionnaire was used as a tool to collect the necessary data for determining the level of these variables. For analyzing the results, two packages (SPSS & AMOS) were used to build the structural equation model (SEM) and extract the required results. The study's results indicated a significant positive relationship between perceived ethical value of the brand and Online Customers’ Shopping Experience through the mediating role of the quality of their relationship with it. The results also showed a meaningful relationship between Employee Resilience and perceived ethical value of the brand through the moderating role of Brand Relationship Quality, indicating that Brand Relationship Quality contributes to improving the customer interaction process by encouraging them to participate in product design and creating a vision that aligns with the needs and desires of customers. Thus, this study places significant emphasis on the behaviors of Iraq Smartphone Users, especially regarding phones (Apple, Samsung, Xiaomi, and Huawei), as well as examining how Brand Relationship Quality can mediate these variables This contributes to improving customer value by building a positive relationship with customers and ensuring the maintenance of providing them with a distinguished experience.